Sudden fear [videorecording (DVD)] - Miller, David, 1909-1992; Crawford, Joan, 1908-1977; Palance, Jack, 1919-2006; Grahame, Gloria; Bennett, Bruce, 1906-2007; Huston, Virginia, 1925-1981; Sherry, Edna (Kino on Video, 1998)
On a train headed home to California, Myra Hudson falls in love with and marries actor Lester Blaine, whom she has just fired from her most recent New York play. Back on her San Francisco estate, something evil appears to be lurking beneath the surface of the couple's idyllic life.